ChemInform Abstract: Chemical and Genetic Studies on Hybrid of Ligularia subspicata and Ligularia cyathiceps Collected in Yunnan Province of China. Issue 12 (March 2015) - Shimizu, Anna; Watanabe, Shizuka; Hanai, Ryo; Okamoto, Yasuko; Tori, Motoo; Gong, Xun; Kuroda, Chiaki
Abstract Five Ligularia samples are analyzed and twenty compounds, including two new compounds (I) and (II), are isolated.